Jewish and Christian liturgy and worship : new insights into its history and interaction / edited by Albert Gerhards & Clemens Leonhard. - Gerhards, Albert; Leonhard, Clemens (Jewish and Christian perspectives series, 2007)
Presents insights into the history and interaction between Jewish and Christian liturgy and worship. This book offers an understanding of the identity of Judaism and Christianity.